A pilot study on a combined non-invasive screening test for metabolic dysfunction-associated steatotic liver disease and type 2 diabetes - Saenger, Katrin; Torres Reyes, Christian; Cahyadi, Oscar; Ebigbo, Alanna; Schmidt, Wolfgang Ekkehard; Quast, Daniel Robert (Frontiers in Endocrinology, 2026)
BackgroundType 2 diabetes (T2D) and metabolic dysfunction-associated steatotic liver disease (MASLD) are increasing globally, with mitochondrial dysfunction being a core component in their development. While a 75g oral glucose tolerance test (OGTT) can be used to diagnose T2D, hepatic metabolic and mitochondrial dysfunction can be assessed using a 13C-methionine breath test (BT). We aimed to evaluate combining these tests for an efficient, non-invasive screening tool.MethodsOn three study days, 26 subjects (11 [43.3%] female, 61± 16 years) subjects underwent either an OGTT, a 13C-methionine BT or both tests combined. Diagnostic outcomes of the individual and combined tests were compared using cumulative 13C percentage dose recovered (cPDR), plasma glucose concentrations and Homeostatic Model Assessment (HOMA)-indexes for insulin resistance and beta-cell function.ResultsIn the combined test, cPDR90min was significantly lower (cPDR90min 2.3± 0.2% vs. 5.7± 0.5%; p< 0.0001), accompanied by a rightward shift of the 13C-increase towards later time points. When breath collection of the combined test was extended, cPDR145min (5.7± 0.4%) was practically identical to cPDR90min of the single test (p= 0.99). OGTT results, plasma glucose, and HOMA-indexes did not differ significantly between tests.ConclusionsCombining a 13C-methionine BT with an OGTT significantly impacts 13C-methionine kinetics, but not OGTT results. A potential mechanism includes a glucose-induced delay of gastric emptying. Combined testing may be feasible when time-adjusted measurements are used, potentially allowing simultaneous screening for both T2D and MASLD-associated mitochondrial dysfunction in clinical practice.